2020
DOI: 10.1039/d0cc06871c
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurement of effective Li–Li scalar coupling constants: the NMR missing link for alkyllithium aggregates

Abstract: Alkyllitium mixed aggregates: dynamics-free value of the 2JLi–Li as a simple access to various structural factors, including the dynamics, solvation and the steric hindrance of alkyl chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Noteworthy for this study are several reported NMR investigations on a series of naphthyllithium compounds [19] and several ortho-dimethylaminoÀ aryllithium compounds [20] in solution. Additionally, there are approaches to utilise 7 Li residual quadrupolar couplings to identify the degree of organolithium aggregation in gels, [21] DOSY, [22] classic 7 Li, [23] and scalar LiÀ Li couplings [24] in NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy for this study are several reported NMR investigations on a series of naphthyllithium compounds [19] and several ortho-dimethylaminoÀ aryllithium compounds [20] in solution. Additionally, there are approaches to utilise 7 Li residual quadrupolar couplings to identify the degree of organolithium aggregation in gels, [21] DOSY, [22] classic 7 Li, [23] and scalar LiÀ Li couplings [24] in NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%